Defectoscopic Susceptibility of Machine Elements - Marian Josko (Communications - Scientific letters of the University of Zilina, 2005)
In the paper defectoscopic susceptibility of machine elements is analyzed. At first, an objective notion is defined and presented in a practical situation. The defectoscopic susceptibility as a feature can be considered and described also as a system consisting of two subsystems and a collection of non-technical factors. The subsystems are defined as a group of many factors. A mathematical structure of selected factors was shown as an example. Some factors of defectoscopic and diagnostic susceptibilities were calculated and gathered for selected parts of a motor vehicle and for air conditioning systems of selected models of cars. The calculated values of those factors enable us to quantitatively assess such features of a machine as its various susceptibilities. They can be practically used in the design, manufacture and maintenance not only of machines, but also of equipment for examination and service of machines and their subassemblies.